Characterization of clinical comorbidities and complications in a group of patients undergoing hemodialysis in a reference institution in Medellin, Colombia. - Martínez-Sánchez, Lina María (2022)
Aim: To characterize the clinical complications and comorbidities presented by patients undergoing hemodialysis in Medellín - Colombia. Materials and methods: Retrospective descriptive observational study, which included hemodialysis patients > 18 years of age who presented some complication associated with the treatment. Non-probabilistic sampling of consecutive cases was carried out. The information was collected from medical records. The analysis was carried out through the IBM SPSS Version 25 program, absolute and relative frequencies were estimated, as well as medians with interquartile ranges. This work had ethical approval. Results: 20 patients were included, of which 60% (12) were male, the median age was 68.5 years and 60% (12) belonged to the subsidized regime. The main pathological antecedents were hypertension in 100% (20), followed by diabetes mellitus in 45% (9). Regarding the replacement therapy time, the median was 25.5 months (Q1: 18.5; Q3: 66). The main associated complications were venous coagulation in 44,4% (12) followed by bleeding in 37% (10) and suspicion of infection in 11.1% (3), most of the bleeding was light. due to decannulation. Conclusion: Renal replacement therapy in general did not represent a high risk of life-threatening complications in patients who underwent it, since most of these adverse effects were considered mild, did not negatively modify quality of life and were easily corrected, similar to that reported in the literature.